Purchasing Power Profile of Milwaukee ZIP Code 53222 - (:unkn) unknown (My University, 2004)
Each year, the U.S. Census Bureau conducts detailed analyses of the spending habits of residents by their household size, type, and income levels. These Consumer Expenditures Surveys are used by marketing firms to estimate expenditures of consumers and to assist retail companies in deciding where to locate and what populations to target for their consumer items and services. In most cases, marketing firms have based their data and recommendations on average household income of residents by geographic locations, while ignoring the advantages of urban density and the concentrated spending that takes place in city neighborhoods. Using a state-of-the-art methodology developed by the Employment and Training Institute, the most recent expenditure survey data are combined with detailed state income tax files disaggregated by family types. These Purchasing Power Profiles offer current and reliable estimates of the spending power of neighborhoods throughout Southeastern Wisconsin. The profiles were provided free of charge, are designed to assist businesses, community organizations, and public officials assess the spending patterns of Milwaukee families and individuals and to help identify neighborhoods that are currently underserved, where residents are required to travel to other areas for their consumer needs.
Keywords: purchasing power; neighborhood assets